Genetic polymorphism on the flexibility of elite rhythmic gymnasts: State of art - Silva, Carla C.; Silva, Lucilene F.; Santos, Camila R.; Goldberg, Tamara B.L. [UNESP]; Ramos, Solange P.; Venancio, Emerson J. (Elsevier, 2019)
Rhythmic gymnastics has been an Olympic sport since 1984, however, there are relatively few studies about this sport. In order to understand whether genetic predisposition could play a role in defining the flexibility phenotype in rhythmic gymnastics, the purpose of this study was to review the current literature and systematically identify common polymorphisms linked to genes correlated with joint mobility in elite rhythmic gymnastics. Systematic computerized searches were performed from 1950 to 2017 in the following databases: Medline, Embase, Cinahl, Lilacs, SPORTDiscus, Web of Science, Scopus and the Cochrane Central. Although the search initially identified 9761 studies, after removing duplicates and excluding by title and abstract, only 10 studies demonstrated potential to be included. After reading of full-texts, 9 studies were entered in the qualitative synthesis, thus only 1 study was eligible for this systematic review. The results of Tringali's study demonstrated that the COL5A1 CT genotype was linked to high joint mobility and to the occurrence of genu recurvatum. From this systematic review, further investigations are suggested to confirm the results of involving genes related to physiological and anthropometric determinants of rhythmic gymnastics performance.
Polimorfismo genético en la flexibilidad de gimnastas rítmicos de la élite: estado de arte
Keywords: Adolescence; Children; Genetics; Gymnastics; Mutation